A Computational Approach for Optimal Control Systems Governed by Parabolic Variational Inequalities (Journal of Computational Mathematics, 2021)
Iterative techniques for solving optimal control systems governed by parabolic variational inequalities are presented. The techniques we use are based on linear finite elements method to approximate the state equations and nonlinear conjugate gradient methods to solve the discrete optimal control problem. Convergence results and numerical experiments are presented.
Keywords: Parabolic variational inequalities; finite elements method; nonlinear conjugate gradient methods.